2023
DOI: 10.1002/pra2.785
|View full text |Cite
|
Sign up to set email alerts
|

In a Perfect World: Exploring the Desires and Realities for Digitized Historical Image Archives

Elina Late,
Hille Ruotsalainen,
Sanna Kumpulainen

Abstract: The primary goal of this paper is to explore users' desires for digitized historical image collections, examining their desires based on different use purposes and information interaction activities. In addition, we investigate the image attributes that users wish to search from the collection. To accomplish this, we conducted 21 qualitative interviews with active users of a digitized historical photograph archive. Our findings suggest that users' desires relate to three contexts: tools, collection, and socio‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…Chassanoff's (2018) study showed that for historical research, photographs provide a valuable historical reference for verification, documentation, or corroboration. Previous research has also focused, for example, on the production and needs for image metadata (Cetinic, 2021;Hanson and Dahlgren, 2022) and studied researchers' image retrieval, especially in the historical domain (Late et al, 2023;.…”
Section: Images As Research Data In the Sshmentioning
confidence: 99%
“…Chassanoff's (2018) study showed that for historical research, photographs provide a valuable historical reference for verification, documentation, or corroboration. Previous research has also focused, for example, on the production and needs for image metadata (Cetinic, 2021;Hanson and Dahlgren, 2022) and studied researchers' image retrieval, especially in the historical domain (Late et al, 2023;.…”
Section: Images As Research Data In the Sshmentioning
confidence: 99%